Evaluation of the amount of nanoparticles emitted in welding fume from stainless steel using different shielding gases - Pacheco, Rita (2017)
The primary objective of this study was to correlate the emission of macro and nanoparticles released during the process of metal inert gas/metal active gas (MIG/MAG) of stainless steel with different gas mixtures. Using different gas mixtures with different heat inputs, it was possible to determine fume formation rates and surface areas of nanoparticles with alveolar lung deposition capacity. It was found, how the various transfer modes and the type of gas protection, in particular, the percentage of active elements in the in the chemical composition of the gas, affect the amount of fumes generated and also the generation of nanoparticles with a high capacity of deposition. The spray transfer mode always shows higher values of nanoparticles surface area, unlike the fume formation rates. Among the tested mixtures 82%Ar+18%CO2 generates higher emissions of nanoparticles as well as fume formation rates.